2013
DOI: 10.1002/nau.22445
|View full text |Cite
|
Sign up to set email alerts
|

Targets for botulinum toxin in the lower urinary tract

Abstract: There is now robust information to support that the mechanism of action of BoNT/A in the bladder involves neurotransmitter release from nerve fibers and urothelial cells. Which neurotransmitter is more relevant is, however, unclear. Likewise, the long duration of effect, the importance of the volume of vehicle injected and the selection of specific injection sites, like the trigone, needs further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 80 publications
0
66
0
Order By: Relevance
“…17 For this reason, cleaved SNAP25 is considered an ideal marker of sites of BoNTA action and, there fore, an important target in future research. 17,18 Despite this apparent accumulation of BoNTA in parasympa thetic nerves, in 2014, the presence of binding protein SV2 as well as the target protein SNAP25 was demon strated within the bladder mucosa using immunohisto chemical staining and western blotting methods. 19,20 This finding indicates that the effects of BoNTA in the urinary bladder are more complex than previously thought, and intravesical delivery of BoNTA into the urothelium by might be both possible and clinically relevant.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 For this reason, cleaved SNAP25 is considered an ideal marker of sites of BoNTA action and, there fore, an important target in future research. 17,18 Despite this apparent accumulation of BoNTA in parasympa thetic nerves, in 2014, the presence of binding protein SV2 as well as the target protein SNAP25 was demon strated within the bladder mucosa using immunohisto chemical staining and western blotting methods. 19,20 This finding indicates that the effects of BoNTA in the urinary bladder are more complex than previously thought, and intravesical delivery of BoNTA into the urothelium by might be both possible and clinically relevant.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…18,21,22 Nowadays, the urothelium is proven to not only act as a barrier but also has important sensory signal ling functions. 23 BoNTA might also alter the release of ATP, neurotrophins and nitric oxide (NO) from the urothelium.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…With strong analgesic properties impairing release of neurotransmitters from nociceptive neurons both at their peripheral and spinal cord endings [94,95], OnabotA injection in the bladder wall has been shown to decrease bladder pain and ameliorate nocturia and frequency in IC/BPS patients refractory to standard treatment [36,96]. Additionally, recent evidence has shown that the analgesic effect after repeated injections of OnabotA is superior to a single injection [97,98].…”
Section: Botulinum Toxin Injectionmentioning
confidence: 99%